2023
DOI: 10.1186/s44167-022-00012-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of compositional analysis studies examining the associations between sleep, sedentary behaviour, and physical activity with health indicators in early childhood

Abstract: Background This systematic review examined if the composition of time spent in sleep, sedentary behaviour, and physical activity of different intensities is associated with health and developmental indicators in children aged 0–5 years. Methods Four electronic databases (MEDLINE, EMBASE, PsycINFO, and SPORTDiscus) were searched in January 2022. Studies were eligible for inclusion if they were peer-reviewed, the average age of participants was < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The national guidelines in many countries including Canada, Australia, and South Africa include consistent recommendations for physical activity; however in some cases these guidelines vary slightly on the age range, covering children from the ages 3–5 years [ 2 – 4 ]. Although the WHO’s guidelines emphasize the importance of 24-hour movement behaviours, an acknowledgment that the whole day matters, individual movement behaviours may confer unique health and developmental benefits [ 5 , 6 ]. Indeed, evidence from a large systematic review shows that engaging in sufficient levels of physical activity is related to several health benefits across domains of physical, social-emotional, and cognitive development [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The national guidelines in many countries including Canada, Australia, and South Africa include consistent recommendations for physical activity; however in some cases these guidelines vary slightly on the age range, covering children from the ages 3–5 years [ 2 – 4 ]. Although the WHO’s guidelines emphasize the importance of 24-hour movement behaviours, an acknowledgment that the whole day matters, individual movement behaviours may confer unique health and developmental benefits [ 5 , 6 ]. Indeed, evidence from a large systematic review shows that engaging in sufficient levels of physical activity is related to several health benefits across domains of physical, social-emotional, and cognitive development [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, evidence from a large systematic review shows that engaging in sufficient levels of physical activity is related to several health benefits across domains of physical, social-emotional, and cognitive development [ 7 ]. More recently, results from multiple compositional data analyses have demonstrated that the relative time spent engaging in physical activity throughout the day, especially MVPA, may be the most beneficial for improving bone and skeletal health, increasing fitness, and developing of fundamental movement skills in young children [ 5 , 6 , 8 , 9 ]. Moreover, physical activity habits begin to develop in early childhood [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sample size calculations were based on detecting a difference of 500 kJ (using SD of 1619 kJ [14]) in daily energy intake (80% power, α 0.05), requiring 85 children. We aimed to recruit 110 children to allow for 20%-40% drop out given the intensive nature of the study [17].…”
Section: Interventionmentioning
confidence: 99%
“…All dietary recall data were entered and cross-checked by registered dietitians using the "Food-Works" dietary analysis software program (FoodWorks 9 Professional, Version 9.0. Brisbane: Xyris Pty Ltd, 2019) which incorporates the New Zealand Food Composition Tables [14]. Dietary intake from the two relevant recalls in each intervention week were adjusted to represent usual intake for that week using the Multiple Source Method (MSM) [26].…”
Section: Measures During Each Intervention Weekmentioning
confidence: 99%
See 1 more Smart Citation